Strategies Used in Teaching Speaking: A case of six EFL Teachers at Junior High Schools in Moa Island - Lekusa, Vecky; Lewier, Christian Albert; Meyer, Fredi (Koli Journal : English Language Education, 2021)
Speaking is one of four basic skills which signifies the level of mastery in English language learning. A foreign language teacher can be considered as fully capable in his journey of teaching when he can enable his learners to speak the language satisfactorily. Thus, his strategies for teaching this language skill is pivotal. Teachers have to choose the appropriate strategies to be applied in speaking class in order to motivate the students as well as promote the acquisition of speaking ability. The present study was designed to find out types of strategies commonly used by EFL teachers and how do these teachers perceive the use of each strategy they were applying in teaching speaking. The teachers apparently teach students who notably restricted by some prohibiting factors to language learning development. In collecting the data a case study was used as an approach to describe the condition. Six EFL teachers at Junior High schools in Moa Island were observed and were asked to fill the questionnaire and were involved in an interview. The results of this study show that the teachers applied several strategies in teaching speaking such as story telling, picture describing, role play, games, and drilling. From those strategies, role play was perceived to be the most common strategy and frequently used by the EFL Moa Island teachers in teaching speaking. All in all, these teachers strongly agree that speaking strategies contributed greatly in improving the students’ speaking ability and so attractive to the students' interest in learning English especially speaking. Class dynamic was significantly high when various strategies were applied in speaking learning activities